PEMETAAN PENELITIAN SEPUTAR COMPANY VALUE : ANALISIS BIBLIOMETRIK VOSVIEWER DAN LITERATUR REVIEW - Devi Oktaviani; Sri Andriani; Sulis Rochayatun (Program Studi Akuntansi, Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy Situbondo, 2025)
This study used VOSviewer bibliometric analysis and literature review studies to map research and advances of scientific publications related to firm value. The research methodology combined qualitative approaches for literature review studies and quantitative methods for bibliometric analysis. It was then conducted by searching the Publish or Perish website for five years, from 2020 to 2025, using the keyword